A Survey of Economic Policies and Macroeconomic Performance in Chile and Colombia, 1970-95 - Clavijo, Sergio (IMF Working Papers; Working Paper ;, 1995)
This survey describes the timing and main macroeconomic results of the ambitious structural reforms adopted by Chile in the middle and late 1970s and by Colombia almost a decade later in the late 1980s and early 1990s. These reforms have enabled both countries to maintain vigorous real growth rates during the first part of the 1990s. However, they face challenges to their competitiveness as their real exchange rates continue to appreciate and real unit labor costs have been increasing. Although their exchange rate management system has helped to avoid an excessive inflow of short-term capital, interest rate differentials keep exerting pressures. Structural reforms have helped attract foreign direct investment, allowing the investment ratios of both countries to increase.